Synthesis and characterization of the structural, microscopic and magnetic properties of FeNi nanoparticles synthesized via the sol-gel method - Rodriguez Martinez, Marco Antonio (2019)
Tese (doutorado)—Universidade de Brasília, Instituto de Física, Programa de Pós-Graduação em Física, 2019.